Investigation of Multiple Transceiver System for Free Space Optical Communication - Li Zhi, Tan; King Ung, Hii; Kon, Cynthia; Chuan, Kong Jer (International Journal of Integrated Engineering, 2020)
In free space optical (FSO) communication, atmospheric turbulence has major impact on the stability of a free space optical transmission system. Laser beam with high coherency and intensity is commonly used to increase the transmission distance. However, with an increased distance, the stability of the system becomes more sensitive to the turbulence. In this work, a multiple transceiver system with signal summing approach is implemented to improve signal transmission stability. The performance of the proposed system is investigated with the intensity turbulence modeled. In comparison with the single transceiver system, the proposed system showed higher signal-to noise ratio and lower bit-error-ratio with doubled stability in terms of the improvement factor.